An analytical method for the quantitative determination of iron ion chelating capacity: development and validation - Santos, Éverton da Silva; Teixeira, Leticia de Melo; Castro, Juliana Cristina; Mardigan, Laura Paulino; Santos, José Rivaldo dos; Gonçalves, José Eduardo; Oliveira, Arildo José Braz de; Gonçalves, Regina Aparecida Correia (Acta Scientiarum. Biological Sciences, 2022)
Iron is a fundamental microelement for human life; however, deficiencies or excesses of these metal ions can cause severe complications and mortality. Chelators are compounds that bind and inhibit iron. Ultraviolet-visible (UV-vis) spectrophotometric methods are key analytical tools in the identification of chemical entities, with the benefits of having good precision and accuracy, and the equipment being easily available as well as quick and simple to implement. In this study, we aimed to provide an alternative, cheaper method for the quantification of iron ion chelation by substituting ferrozine for gallic acid and validating its use with UV-vis according to official ANVISA and ICH guidelines. The parameters assessed were specificity, linearity, precision, accuracy, robustness, and finally, the percentage of iron ions chelating was calculated. The results demonstrated that this method was accurate, simple, specific, selective, precise, and reproducible, and was successfully validated for the determination of iron ions chelating. The percentage of iron ions chelating, promoted by the standard chelator EDTA, was 45% and 47% for Fe2+ and Fe3+, respectively. It is concluded that this new method is beneficial in terms of its simplicity, rapidness, low cost, and the fact that it produces very low levels of dangerous residues.